CONSTRUCTING OF THE SUN CONCENTRATOR AND INVESTIGATING HEATING FEATURES (International journal of artificial intelligence, 2024)
This article deals with the experienced results of a paraboloid-type concentrator designed as a solar kitchen for personal use.